Impact of COVID-19 on University Supervision and Programme Accreditation in Nigerian Universities - Adanna, Chinwuba Mary; Emmanuel, OLAOYE, Abiodun; Yakubu, Isah (Researchparks Publishing, 2023)
The study assessed the impact of COVID-19 lock down on universities supervision and programme accreditation in the Nigerian universities using North east zone as case study. Survey research design was adopted for the study. The population of the study was made up of all the academic staff in the study area of North East Nigeria. Simple random sampling technique was employed to select 200 academic staffers in four public universities in the study area which was used as study sample. A self-developed questionnaire was designed called (Perception of Academic Staff on Impact of COVID-19 on universities supervision and programme accreditation Questionnaire” (PASIUSPAQ). The instrument was subjected to reliability test using the split- half estimated method to ascertain the internal consistency of the instrument. The reliability estimate for the subscale and the full test ranged from 0.59 to 0.76, which shows that they were valid. Data collected was analyzed by ANOVA. The result showed that COVID-19 lock down affected universities supervision in Nigeria. The result also revealed that COVID-19 lock down affected programme accreditation in Nigerian universities. Based on this findings, the study recommended adoption of e-supervision and e-programme accreditation by the respective institutions in charge of universities supervision and accreditation in Nigeria.